Synthesis and Characterization of New 1,2-Dihydropyridine-3-Carbonitrile Compounds with Study of Expected Biological Activity - Ibraheem, Hiba H; Al-Majedy, Yasameen K; Salim, Ali J; Al-Bayat, Redha I (Al-Nahrain Journal of Science, 2018)
New 1,2-dihydropyridine-3-carbonitrile derivative compounds (3,4) were synthesized by cyclization of ketones (compound (1) and compound (2)) with appropriate aldehydes (4-N, N-dimethylaminobenzaldehyde and 4-chloro-2-oxo-2H-chromene-3-carbaldehyde) in presence of ethyl cyano acetate and ammonium acetate. The new synthesized compounds have been characterized using Melting point, FT-IR spectroscopy and 1H-NMR and 13C-NMR spectrum. The evaluation of biological activity of some synthesized compounds (1-4) with different concentration 10 mg mL−1, 1 mg mL−1 and 0.1 mg mL−1, against two types of bacteria on gram positive bacterial Staphylococcus aureus, Streptococcus pyogenus and gram nagetive bacterial Escherichia coli, Klebsiella pneumniae.